Cardiac rhabdomyosarcoma mimicking a mediastinal tumor and the role of endoscopic ultrasonography - Pesenti, Christian (Medknow Publications & Media Pvt Ltd, 2012)
We report a case of cardiac rhabdomyosarcoma, with initial clinical features of “atrial rhythmic dysfunction”, which was concluded as a mediastinal tumor by computed tomography (CT) scan. Endoscopic ultrasonography (EUS) and EUS-FNA (fine needle aspiration) were initially conducted to diagnose the isolated mediastinal mass. In this case, EUS re-assessed the previous diagnosis as a cardiac tumor, and the patient eventually achieved a 17-month survival rate after chemotherapy. In this paper, EUS findings obtained in our case are described and a review of literatures is briefly discussed. We also describe the advantages and limitations of this technique compared with other image diagnosis alternatives.